Dinamika aktivitas penangkapan ikan dan pendapatan nelayan disekitar kegiatan pertambangan Desa Batuawu Kecamatan Kabaena Selatan Kabupaten Bombana - Sidiq, Azwar; Arsal, La Ode Muhammad; Risfandi (Universitas Halu Oleo, 2023)
Mining activities have caused damage to ecosystems in coastal areas and disruption of fishing activities. This study aims to determine the dynamics of fishing activities, income levels, and adaptation strategies of Batuawu Village fishermen due to mining activities. Respondents were taken using the census method, as many as 18 Fishing Households (RTP). The data were analyzed using quantitative descriptive analysis. The results showed that fishing activities were generally carried out by